Corrosion suppression of aluminium current collectors within Li-ion cells using 3-methoxypropionitrile-based electrolytes. (1st November 2022) - Yen, Chih-Han; Neale, Alex R.; Lim, Jungwoo; Bresser, Dominic; Hardwick, Laurence J.; Hu, Chi-Chang
Abstract: Electrolytes containing lithium bis(trifluoromethylsulfonyl)imide (LiTFSI) as the conductive salt generally possess the high moisture tolerance and innate HF-free generation in moisture environments in comparison with those containing lithium hexafluorophosphate (LiPF6 ). However, severe corrosion of the aluminium current collector presently hinders the use of LiTFSI within Li-ion cells. Here 3-methoxypropionitrile (MPN) is introduced as an alternative, non-toxic solvent into the electrolyte formulation to explore the effects on Al corrosion. The MPN-containing electrolytes can suppress Al corrosion via the generation of an aluminium nitride dominated protection layer during charge-discharge cycling, as confirmed by X-ray photoelectron spectroscopy. For the cycling performance of Li||LiNi0.6 Mn0.2 Co0.2 O2 half cells, the increasing addition of MPN solvent improves capacity retention and suppresses the corrosion of Al current collectors in LiTFSI containing electrolytes.